Teori Permintaan Dalam Ekonomi Islam: Prinsip, Konsep, Dan Implementasi - Delia, Dwi Anisa; Hidayati, Qonita; Winario, Mohd (EL-EMIR Institute, 2025)
This study aims to explore the theory of demand in Islamic economics by reviewing its principles, concepts, and implementation in modern economic life. The research approach uses a qualitative method with literature analysis covering primary and secondary sources, such as the Qur'an, Hadith, and classical and contemporary Islamic economic literature. The results of the study indicate that the theory of demand in Islamic economics is based on moral and ethical principles that emphasize justice, balance, and public welfare. Consumer demand in Islamic economics is not only influenced by economic factors such as price and income, but also by spiritual values, such as priority needs, prohibition of excessive consumption (israf), and prohibition of haram goods. In addition, the implementation of the theory of demand in Islamic economics can be realized through policies that encourage the production and consumption of halal and tayyib goods, promotion of ethical awareness in consumption, and strengthening zakat and waqf institutions to support economic redistribution. This study recommends strengthening education related to the principles of Islamic consumption to the community and developing a policy framework that supports the implementation of Islamic values ​​in the modern economic system. The implementation of these values ​​is expected to create a balance between the interests of individuals and society, and contribute to the sustainability of the global economy.